DEM modelling of non-spherical particle breakage and flow in an industrial scale cone crusher. (April 2015) - Delaney, G.W.; Morrison, R.D.; Sinnott, M.D.; Cummins, S.; Cleary, P.W.
Highlights: A new breakage method for non-round particles is proposed for DEM. Progeny distributions use the t 10 method and data from breakage testers. The model is successfully applied to a cone crusher predicting realistic flow. Particles break by compression as they approach the choke point of the crusher. The predicted product size distribution includes resolved and unresolved components. Abstract: Predictions of particle flow and compression breakage of non-round rock passing through an industrial scale cone crusher are presented. The DEM (Discrete Element Method) particle breakage model is generalised to allow non-round particles to be broken into non-round progeny. Particles are broken in this DEM model when the elastic energy of a contact is sufficiently high to initiate fracture. Progeny size distribution data from JKMRC Drop Weight Test (JKDWT) or JKMRC rotary breakage test (JKRBT) is used to generate the specific daughter fragments from each breakage event. This DEM model is able to predict the production of both coarser progeny which are resolved in the DEM model and finer progeny which are not. This allows the prediction of product down to very small sizes, limited only by the fineness of the fragments measured in the breakage characterisation. The predicted flow of material through the crusher, product size distribution and liner wear are discussed. The generalised breakage model demonstrated here is suitable for modelling all forms of crushers.